Juices enriched with phenolic extracts from grapes - Jana KULICHOVÁ; Mantana BUAONG; Josef BALÍK; Pavel HÍC; Jan TŘÍSKA (Czech Journal of Food Sciences, 2018)
The paper describes the preparation and evaluation of phenolic extracts from waste materials - pomace (grape marc), seeds and press oil cake of the white grape variety Irsai Oliver (Vitis vinifera L.) and their addition to apple and grape juices to increase the nutritional properties. The waste samples were extracted using 50 or 80% ethanol (v/v). Some of the samples were extracted for 60 min at boiling temperature under reflux; the remainder were processed for 24 h on a shaker at room temperature. The highest antioxidant capacity (as measured using DPPH (758 ± 28 mM Trolox/kg of extracted matter)) and content of total polyphenols (74 ± 0.7 g gallic acid/kg of extracted matter) were found in the extract of the seeds obtained through extraction using 50% ethanol (v/v) at boiling temperature for 60 minutes. The press oil cake extract obtained by means of 80% ethanol (v/v) at boiling temperature for 60 min was evaluated as the best for enriching the sensory quality of apple and grape juices. The addition of 1 g of freeze-dried press oil cake extract to 1 l of juice increased the antioxidant capacity and total polyphenol content two-fold